Localizing Mimpi through the artistry of Orang Ulu motifs in the set design - Nur Syarafina Suhaimy; Nur Qasdina Jeeta Abdullah (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
The definite definition of scenography is debatable up until today. Despite the many interpretation and definitions given by theatre practitioners from all over the world, there are some categories of design under that lie under this term. They are scenic design, costume, lighting and sound. This research proposes to look for new ideas in creating the world of a play in scenic design of an intercultural theatre. This thesis aims to explore the adaptation of Sarawakian motifs, specifically Orang Ulu’s into the set design of Mimpi. Through the adaptation of the motifs into the set design of Mimpi, the data acquired are collected and analysed through the qualitative and quantitative approach.